Investigation of the smelting reduction mechanism and of iron extraction from high-iron red mud - Kun Wang; Yan Liu; Ting-an Zhang; Xiao-fei Li; Xin Chen (Materials Research Express, 2020)
High-iron red mud presents a problem due to its alkalinity which leads to significant risks to the environment. In order to realize the harmless and large-scale utilization of high-iron red mud, the smelting reduction experiments were carried out to investigate the reaction mechanism for extraction iron from high-iron red mud. FactSage 6.4 software was used to conduct thermodynamic analysis of the carbon thermal reduction system. The results showed that the direct reduction with carbon involved a process of Fe _2 O _3  → Fe _3 O _4  → FeO → Fe, in which the theoretical required molar ratio of C/O (oxygen in Fe _2 O _3 ) was 1:1. The maximum degree of iron extraction was 92.8% with anthracite as reductant and 88.8% without anthracite smelting at 1500 °C for 30 min in a graphite crucible. XRD was conducted to analyze the mineral phase of the samples and slags. The results showed that the minerals contained in high-iron red mud were hematite, quartz, rutile, and sodium aluminosilicate hydrate. The blank sample was consisted of hematite, nepheline quartz, and the reduced slag without quenching consisted of perovskite and gehlenite, indicating that the reaction processes occurred from sodium aluminosilicate hydrate to nepheline and then occurred from nepheline to gehlenite in slagging process. The overall smelting reduction process was described as three mass transfer steps and three chemical reaction steps. These results provide useful information for large-scale and harmless utilization of high-iron red mud.